Sistem Informasi Ujian Online Tryout Berbasis Web Di Bimbingan Bela-jar Mystaners Bintaro Jakarta Selatan - Muhammad Faisal Natsir Asrofi; Wahju Tjahjo Saputro; Hamid Muhammad Jumasa (Universitas Muhammadiyah Purworejo, 2020)
MyStaners is a tutoring institution that focuses on educational courses for candidates of new student admission selection (SPMB) in Politeknik Keuangan Negara (PKN) STAN. MyStaners wants to build web-based tryout online examination services. In this research will be built web-based tryout online examination services information system with the scheme type of questions and assessment test that appropriate with SPMB PKN STAN. This web-based system is built with the PHP programming language, Codeigniter framework, and MySQL database.